BLENDED LEARNING STRATEGIES IN TEACHING ENGLISH GRAMMAR TO NON-NATIVE SPEAKERS - Allayorova Zebiniso Boymuartovna; Elboyeva Shaxnoza Azim qizi; Yuldoshova Shaxlo Yaqub qizi (TADQIQOTLAR, 2025)
Abstract  Blended learning  combines traditional  face-to-face instruction  with digital resources, enhancing the learning experience for non-native English speakers. This  article  explores  various  blended  learning  strategies  specifically  designed  to improve English grammar instruction. It discusses the advantages, challenges, and best practices in implementing a blended approach to teaching grammar effectively.